Review of computer models for fabric simulation - Jevšnik, Simona (Tekstilec, 2014)
3D computer technologies are closely linked to all textile fi elds ranging from the designing and constructing of fabrics and garments, virtual human body presentations, interactive virtual prototyping to virtual fashion shows and e-trading. This paper off ers a review of frequently used methods for fabric simulation. The review is divided into two parts. The fi rst part of the paper comprises currently used techniques, followed by the presentation of basic terms and fabric parameters required for fabric simulations. The second part discusses the approaches and methods for constructing computer models of fabrics. In conclusion, the list of used techniques and parameters for defi ning a computer fabric model are presented together with given future guidance.
Keywords: CAD/CAM; modeli tekstilij; simulacije tekstilij; tekstilstvo